Terapi Manual Dan Terapi Latihan Meningkatkan Kemampuan Fungsional Pada Kasus Cervical Syndrome Et Causa Flat Neck : Studi Kasus - Djawas, Faizah Abdullah; Huwaida, Rafiqoh Nur (UI Scholars Hub, 2022)
Cervical syndrome is a collection of symptoms, especially pain around the cervical spine. Pain in cervical syndrome is more common in conditions related to the deformity of the cervical vertebrae, one of which is a flat neck or conditions where cervical lordosis is reduced. When the lordosis curve disappears, the vertical load will be redistributed along the anterior portion of the cervical spine, causing pressure on soft tissue and surrounding bone. This can lead to various musculoskeletal problems. The combination of manual therapy and exercise is suggested to reduce problems such as pain, limitations of the range of motion (ROM), and improve functional ability. Methods: Single case study, with the implementation of kneading and friction massage and exercise therapy in the form of modified cervical and shoulder retraction exercises, evaluated eight times. pain Visual Analogue Scale (VAS), goniometer, and the Neck Disability Index (NDI) parameter were used for pain intensity, ROM, and functional ability, respectively. Results: There was a decrease in the VAS for pain intensity, compared to the first evaluation for right lateral flexion of 7.6/10 to 1.2/10, left lateral flexion from 7.3/10 to 0.9/10, and the right rotation from 6.1/10 to 0/10. In addition, there was an increase in ROM compared to the first time. The ROM for extension motion increases from 40º to 45º, right lateral flexion 35º to 40º, left lateral flexion 40º, and right rotation from 50º to 60º. Associated with a decrease in VAS and an increase in ROM, the NDI score shows significant improvement from 44% in the first evaluation to 2% in the last evaluation. The decrease in the NDI value indicates the better the patient's functional ability. Conclusion: This study shows that massage and exercise therapy in the form of modified cervical and shoulder retraction exercises are proven to be effective in reducing pain, increasing ROM, and improving functional abilities.